Factors associated with motivation to avoid meeting family and friends during the COVID-19 pandemic. (20th October 2021) - Goes, AR; Soares, P; Moniz, M; Gama, A; Pedro, AR; Laires, P; Dias, S; Nunes, C
Abstract: Background: The widespread adherence to behaviours that prevent the transmission of the SARS-CoV-2 virus depends on human will. There is a paucity of research on the factors that influence adherence to social distancing. Available research suggests that it varies with the specific behaviour and that reducing contact with family and friends is the hardest one. This study aims to identify factors associated with motivation to avoid meeting with family and friends during the second lockdown of the COVID-19 pandemic in Portugal. Methods: We used data from a community-based survey, "COVID-19 Barometer: Social Opinion", which includes sociodemographics, psychosocial variables, and subjective health and wellbeing indicators from 20th February to 19th March 2021. We included 1336 participants who answered the question "To what extent is it easy for you to avoid visiting family and friends?". Logistic regression analysis was used to identify factors associated with difficulty to avoid visiting family and friends. Results: Preliminary data shows that 38.4% (513) had difficulties avoiding meeting with family and friends. Those with greater difficulty were the ones who have less education, higher negative emotionality, do not work remotely, have more difficulties to stay home and practice physical distancing and consider the Government's measures inadequate. Contrarily, those who have less difficulty avoiding visiting friends and family are older and have low risk perception of COVID-19 infection. Conclusions: This study suggests higher difficulty in avoiding visiting friends and family for those whose routines demand not staying at home, with low agreement with Government measures, and struggle with higher negative emotionality, confirming the personal costs of these behaviours and the importance of habits. Older people had less difficulty, suggesting that these measures may be closer to their usual routines. Interventions should consider the specificities of social interaction. Key messages: Social distancing comes at an enormous cost to people's livelihoods and it also depends on people living circumstances. Interventions to improve adherence to social distancing should consider the specificity of social interaction and the potential dissonance created by the overall routines.